A high five for Glenn Burke - Bildner, Phil (Square Fish, 2021)
After researching Glenn Burke, the first major league baseball player to come out as gay, sixth-grader Silas Wade slowly comes out to his best friend Zoey, then his coach, with unexpected consequences.